2022
DOI: 10.3390/ijms23116355
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Deleterious Effects in Gastric Epithelial Cells and Vascular Endothelial Cells In Vitro in the Milieu of Helicobacter pylori Components, 7-Ketocholesterol and Acetylsalicylic Acid

Abstract: The Gastric pathogen Helicobacter pylori (HP) may influence the development of coronary heart disease (CHD). H. pylori induce reactive oxygen species (ROS), which transform cholesterol to 7-ketocholesterol (7-kCh), a CHD risk factor. Acetylsalicylic acid (ASA)—an Anti-aggregation drug used in CHD patients—may increase gastric bleeding and inflammation. We examined whether H. pylori driven ROS effects in the cell cultures of gastric epithelial cells (AGS) and vascular endothelial cells (HUVEC) progress in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…It could be due to domination of a T helper 2 lymphocyte response in CHD patients, which promotes the antibody production 67 . It is also possible that prophylactic usage by CHD patients of acetylsalicylic acid (ASA) as antiaggregating factor, due to its’ local cytotoxicity, can increase the penetration of H. pylori antigens through epithelial barrier and increase their systemic availability to immunocompetent cells 30 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It could be due to domination of a T helper 2 lymphocyte response in CHD patients, which promotes the antibody production 67 . It is also possible that prophylactic usage by CHD patients of acetylsalicylic acid (ASA) as antiaggregating factor, due to its’ local cytotoxicity, can increase the penetration of H. pylori antigens through epithelial barrier and increase their systemic availability to immunocompetent cells 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Searching for biomarkers linking H. pylori infection and CHD is important for therapeutic reasons 24 . In our previous studies conducted in vitro on gastric epithelial cells and vascular endothelial cells we showed that H. pylori components may be involved in the elevation of proatherogenic inflammatory response corelated with induction of oxidative stress, which may provide environment for oxidation of LDL a classic risk factor of CHD 30 . H. pylori also upregulates the level of homocysteine, which in excess is pro-atherogenic 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is initiated by the stimulation of gastric mucosa barriers by toxic components of H. pylori , such as vacuolating cytotoxin, urease, and lipopolysaccharide (LPS) 44 . This continuous infection leads to the generation of reactive oxygen species (ROS) and the subsequent formation of oxidized low‐density lipoprotein (oxLDL), involving the transformation of cholesterol into 7‐ketocholesterol (7‐kCh) 44 . Notably, exposure of AGS cells to 7‐kCh in the culture medium significantly increases the levels of ROS, IL‐8, and triggers cell apoptosis.…”
Section: Metabolic Pathways Alterationsmentioning
confidence: 99%
“…Overall, it has been documented that multiple cytotoxic factors of H. pylori can exacerbate oxidative stress of epithelial cells, such as the CagA, VacA, and GGT. CagA has been found to localize to mitochondria and trigger ROS production in gastric epithelial cells, 49 but the precise mechanism remains unclear. Moreover, recent investigations proposed that the presence of cagA + H. pylori strains can elevate the levels of spermine oxidase, an enzyme that facilitates the transformation of the polyamine spermine into spermidine, consequential resulting in more H 2 O 2 production, DNA damage as well as cell apoptosis in gastric epithelial cells 50 .…”
Section: Oxidative Stress Generationmentioning
confidence: 99%